Environmental health and justice screening tools: a critical examination and path forward - Osakwe, Nnamdi C.; Motsinger-Reif, Alison A.; Reif, David M. (Frontiers in Environmental Health, 2024)
This manuscript critically examines the landscape of public-facing web-based environmental health (EH) and environmental justice (EJ) screening tools aimed at mitigating environmental health crises that are involved in a substantial percentage of deaths globally. These EJ/EH screening tools have proliferated with the growth of publicly available data sources and computational advances that have fueled novel analytics and have made strides toward democratizing access to EJ/EH information impacting communities. The interactive, highly visual analytics offered by some of these EJ/EH screening tools could help address the role of environmental injustice in exacerbating environmental health-related causes of mortality and enable affected communities to take a more active role in EJ/EH efforts. Environmental injustice results from environmental conditions that affect communities differently based on residents’ race, income level, national origin, and level of participation in decision-making processes. We survey existing EJ/EH screening tools and evaluate selected examples based on parameters that include data availability, characterization of environmental burden and vulnerability, evaluation of stressor levels, and interpretability of environmental health and justice scores. This review highlights the unique capabilities and limitations of EJ/EH screening tools used at the local (US-Centric), national (US-Centric), and international levels. We then discuss unmet needs and thematic limitations apparent in this survey, related to data availability, relevancy of stressors, assignment of indicator weights, threshold values for action and intervention, modeling robustness, and appropriate community focus. The results underline the need for robust, accessible, and community-centric EJ/EH screening tools that can effectively address the unique environmental health burdens and vulnerabilities faced by communities. We conclude with proposed strategies to enhance EJ/EH screening tool development.